Characteristics of oil palm empty fruit bunch fiber and mechanical properties of its unidirectional composites. Issue 3 (9th March 2018) - Cheng, Teo Siew; Uy Lan, Du Ngoc; Phillips, Steven; Tran, Le Quan Ngoc
Abstract : The characteristics of waste oil palm empty fruit bunch fiber (OPEFB) including fiber morphology and mechanical properties were investigated for use as reinforcement in polymer composites. The mechanical properties of the OPEFB fiber were determined by the single fiber tensile test which was carried out at different span lengths (20, 40, and 60 mm) to obtain the reliable strength and stiffness of the fiber. The extrapolated E‐modulus at infinite fiber length was found to be around 4.36 GPa. The fiber strength was in the range of 150–190 MPa. The unidirectional (UD) composite of OPEFB fibers in various polymer matrices, namely polypropylene, poly(lactic acid), and epoxy, were prepared and characterized. Three‐point bending test (3PBT) was performed on the UD composites in both fiber transverse and longitudinal directions to determine fiber‐matrix interfacial adhesion and composite flexural properties, respectively. Besides, It was found that the efficiency factors achieved for OPEFB in poly(lactic acid) and epoxy were 0.72 and 0.87, respectively, which were significantly higher than that of OPEFB in polypropylene. This result was consistent with the interfacial strength measured by transverse 3PBT. The study provides fundamental understanding for design and application of OPEFB in polymer composites. POLYM. COMPOS., 40:1158–1164, 2019. © 2018 Society of Plastics Engineers